APPLICATION OF ACOUSTIC IMPEDANCE INVERSION TO PREDICT THE “Y” FIELD RESERVOIR DISTRIBUTION - Komara, Eki; M.E.P, Desak Putu; Miftakhul F, M Haris; Satriana, Satriana (Institut Teknologi Sepuluh Nopember, 2024)
Identification of accurate reservoir distribution is necessary to identify prospective and productive zones. One way to identify the distribution of reservoirs in the